Exploration of Mode Choice Behavior for Regular and Short Distance Travel in a Developing Country (Journal of Engineering Science, 2024)
The study of mode choice behaviour is receiving a considerable interest in Bangladesh like in other developing countries. Hence, a questionnaire survey of 514 citizens in Chittagong city was conducted to explore mode choice behaviour for short distance and regular travel. Multinomial Logit Model (MNL) was used to assess the factors involved for various mode choices. Gender, age, profession, education, level of income, household type, vehicle ownership, and distance to a stopping spot all seem to be factors that have been found to be important for short-distance and regular travel using the MNL model according to a utility function. The major findings indicates that the majority of the people prefer the bus both for short and regular distance travel, whereas high earners choose the cars for regular travel.Journal of Engineering Science 15(1), 2024, 59-73